2015
DOI: 10.1038/ncomms9804
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis identifies seven susceptibility loci involved in the atopic march

Abstract: Eczema often precedes the development of asthma in a disease course called the ‘atopic march'. To unravel the genes underlying this characteristic pattern of allergic disease, we conduct a multi-stage genome-wide association study on infantile eczema followed by childhood asthma in 12 populations including 2,428 cases and 17,034 controls. Here we report two novel loci specific for the combined eczema plus asthma phenotype, which are associated with allergic disease for the first time; rs9357733 located in EFHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 70 publications
(87 reference statements)
6
114
0
7
Order By: Relevance
“…Studies of the application of skin emollients to maintain skin barrier integrity have shown beneficial effects in terms of atopic dermatitis, but they have not yet focused on the development of food allergies 121,122 . Genetic studies have identified seven susceptibility loci that are associated with the atopic march from atopic dermatitis to asthma, but their role in susceptibility to food allergy was not studied 123 . Further investigation of the extent to which the prevention and treatment of atopic dermatitis may also function in food allergy prevention and treatment may be very valuable.…”
Section: Preventionmentioning
confidence: 99%
“…Studies of the application of skin emollients to maintain skin barrier integrity have shown beneficial effects in terms of atopic dermatitis, but they have not yet focused on the development of food allergies 121,122 . Genetic studies have identified seven susceptibility loci that are associated with the atopic march from atopic dermatitis to asthma, but their role in susceptibility to food allergy was not studied 123 . Further investigation of the extent to which the prevention and treatment of atopic dermatitis may also function in food allergy prevention and treatment may be very valuable.…”
Section: Preventionmentioning
confidence: 99%
“…However, asthma also has a high rate of AR co-morbidity 4 , which makes it necessary to weigh the effects of both AR and eczema. Indeed, the lack of data regarding AR was acknowledged as a limitation in a recently published meta-analysis focused on progression from eczema to asthma 5 . Herein, we elucidated the associations between KIF3A SNPs and asthma, eczema, and AR, alone and in combination, in the Greater Cincinnati Pediatric Clinic Repository (GCPCR), a well-phenotyped biorepository of over 7000 children, and controls from the Genomic Control Cohort (GCC), a population-based cohort of 1,020 children.…”
Section: To the Editormentioning
confidence: 99%
“…Some genome-wide association studies, point to the fact that FLG could partially tag some other mutations like those near LCE3E (rs61813875) [51,52] and according to this, we think that it might be important to study other polymorphisms in genes from the EDC complex namely FLG (loss-of-function mutations (R501X and 2282del4), in order to more accurately understand the importance of this complex in asthma, AD or other allergic diseases.…”
Section: Discussionmentioning
confidence: 90%